Iocn 2018 2018
DOI: 10.3390/iocn_2018-1-05191
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effects of Nanoparticle Incorporation on the Mechanical Properties of Hydrogels

Abstract: Recent studies have expanded our understanding of the effects of nanoparticles on hydrogel mechanical properties. However, further studies are needed to validate the generality of these findings, as well as to determine the exact mechanisms behind the enhancements afforded by the incorporation of nanoparticles. In this study, we performed rotational rheological characterizations of chemically crosslinked poly(acrylamide) hydrogels incorporating silica nanoparticles to better understand the role of nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…To achieve the desired performance, a better understanding of NP–matrix interactions and the mechanisms involved in the formation of these composite systems is needed. Special attention should be paid to the following: effective incorporation of the NP component to maximize therapeutic loading while maintaining the integrity of each component; tunable mechanical performance to match application-specific requirements; biocompatibility, which is essential in all biomedical applications but may be compromised during gelation or degradation; and long-term stability to minimize treatment frequency [ 81 ]. Achieving a uniform distribution of NPs in HFMs is thus a multidimensional challenge that requires careful consideration of hydrogel formulation, NP properties, and fabrication methods.…”
Section: Hydrogels and Nanoparticles—smart Platforms For Nanotheranos...mentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve the desired performance, a better understanding of NP–matrix interactions and the mechanisms involved in the formation of these composite systems is needed. Special attention should be paid to the following: effective incorporation of the NP component to maximize therapeutic loading while maintaining the integrity of each component; tunable mechanical performance to match application-specific requirements; biocompatibility, which is essential in all biomedical applications but may be compromised during gelation or degradation; and long-term stability to minimize treatment frequency [ 81 ]. Achieving a uniform distribution of NPs in HFMs is thus a multidimensional challenge that requires careful consideration of hydrogel formulation, NP properties, and fabrication methods.…”
Section: Hydrogels and Nanoparticles—smart Platforms For Nanotheranos...mentioning
confidence: 99%
“…Achieving a uniform distribution of NPs in HFMs is thus a multidimensional challenge that requires careful consideration of hydrogel formulation, NP properties, and fabrication methods. Advanced imaging and spectroscopic techniques are valuable tools for characterizing and optimizing NP distribution within the hydrogel matrix, ultimately enhancing the performance of hydrogel microneedle drug delivery systems [ 81 ].…”
Section: Hydrogels and Nanoparticles—smart Platforms For Nanotheranos...mentioning
confidence: 99%
“…Also rheology may be used to determine the mechanisms behind the enhancements afforded by the incorporation of NPs. For example, Zaragoza and Asuri performed rotational rheological characterizations of chemically crosslinked poly(acrylamide) hydrogels with embedded silica NPs [ 84 ]. They found that pseudo-crosslinking, governed by noncovalent interactions between the NPs and the hydrogel polymers, plays an important role in the observed reinforcements.…”
Section: Nanoparticle-hydrogel Compositesmentioning
confidence: 99%